Harmonisasi Antar Umat Beragama Melalui Pernikahan Beda Agama - Munawaroh, Lathifah (FIKRAH, 2017)
Indonesia as the religious community with the six recognized religions makes this country often vulnerable and sensitive in issues related to religion. Further, disharmony among religions is often apparent, even at the level of endless hostility. Keeping the peace by pursuing harmonious efforts among religious people is the duty of Indonesian society. One of the things that make disharmony among religious people is the issue of different religious marriages in Indonesia. This is because religious marriage in Indonesia has become a polemic and issues that need to get attention for all people. For example, the scholars who have issued his fatwa to the legal basis of the law. While there is an ijtihad from contemporary scholars who allow it, Sayyid Sabiq is one of them. This paper aims at analyzing the thoughts of Sayyid Sabiq in the issue of different religious marriages in order to create a harmonious relationship between religious people. This research is a literature by using Fiqhus Sunnah as the primary data in analyzing Sayyid Sabiq’s opinion about the marriage of different religions, especially the marriage of Muslim men with female scribes who allow this type of marriage as an effort of harmonization between religious people, especially Muslims with the scribes.